Development and evaluation of an intervention to improve food and nutrition literacy among Iranian Kurdish primary school children: An application of intervention mapping approach - Ahmadpour, Mohammad; Omidvar, Nasrin; Shakibazadeh, Elham; Doustmohammadian, Azam; Rahimiforoushani, Abbas (Frontiers in Public Health, 2023)
Background: Food and nutrition literacy (FNLIT) is a relatively new term that is used to define the knowledge, skills, and behaviors necessary to achieve a healthy diet. Improving food and nutritional literacy in children is a necessary solution to eliminate nutritional disorders in this age group. The purpose of this study was to design, implement and evaluate an intervention to improve food and nutrition literacy in children aged 10-12 years old based on an intervention mapping (IM) approach. Methods: This experimental study was performed in three phases. Through the first phase, an intervention was developed using the (IM) approach. In the second step, the intervention was implemented for six months, and in the third phase, the intervention outcomes were evaluated and compared with the control group through a randomized controlled trial among 300 participants (each control and intervention group=150) Results: Before the intervention, there was no significant difference between the control and intervention groups in all subscales of FNLIT. After the intervention, there was a significant difference between the control and intervention groups in all subscales of FNLIT (P<0/001). There were no differences between the two groups in terms of the FNLIT scores at baseline (p>0.05). However, after six months of intervention, a significant difference was observed between the two groups (Intra-group differences) (P<0.001). Such a difference was not identified in the control group after six months; also, the results show the impact of socioeconomic factors and parental literacy on the average score of students' FNLIT, and after the intervention, a significant difference was observed between the scores of control and intervention groups in all subscales of the FNLIT (P <0.001). Conclusions: The school-based intervention developed and evaluated in this study provides a basis for future programs targeting the improvement of FNLIT in children, especially in poor and deprived areas such as Kurdistan province. Trial registration: Iranian Clinical Trials Registry (IRCT) Code: 32094- date: 14.07.2018